3(-2x+1)-4(-x)=x+19

Simple and best practice solution for 3(-2x+1)-4(-x)=x+19 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(-2x+1)-4(-x)=x+19 equation:


Simplifying
3(-2x + 1) + -4(-1x) = x + 19

Reorder the terms:
3(1 + -2x) + -4(-1x) = x + 19
(1 * 3 + -2x * 3) + -4(-1x) = x + 19
(3 + -6x) + -4(-1x) = x + 19

Remove parenthesis around (-1x)
3 + -6x + -4 * -1x = x + 19

Multiply -4 * -1
3 + -6x + 4x = x + 19

Combine like terms: -6x + 4x = -2x
3 + -2x = x + 19

Reorder the terms:
3 + -2x = 19 + x

Solving
3 + -2x = 19 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
3 + -2x + -1x = 19 + x + -1x

Combine like terms: -2x + -1x = -3x
3 + -3x = 19 + x + -1x

Combine like terms: x + -1x = 0
3 + -3x = 19 + 0
3 + -3x = 19

Add '-3' to each side of the equation.
3 + -3 + -3x = 19 + -3

Combine like terms: 3 + -3 = 0
0 + -3x = 19 + -3
-3x = 19 + -3

Combine like terms: 19 + -3 = 16
-3x = 16

Divide each side by '-3'.
x = -5.333333333

Simplifying
x = -5.333333333

See similar equations:

| 3t+2(t+1)+7t+6=-16 | | 3x+6=3x-12 | | 7m-25=-32+6m | | z-42=-41 | | 20=5c-3 | | 2(x-3)=3x+3 | | x-0.6=9.36 | | 7e-9=19.7 | | ax=5a | | n^3-n=7n^2-5 | | n^3-n=7n^2-5 | | 3x=b/a | | 17(3)= | | 7p=50.4 | | 8x+14=12x-22 | | 3(x+5)+4(x-3)-6x=4 | | 17m=170 | | (x)(x+8)=96 | | 120-4x=40 | | 12-5x=-58 | | 7+9x=97 | | A(6a-3)= | | 2+8x=66 | | 6/2X+14 | | 11-4*x+1-3=11+2*4-2x-16 | | 7x-2=103 | | 3.5(c-8)+c=125 | | 6/(2X)=14 | | 9=6x-15 | | 2*4-2*3-x-1=4*2*4x-3+7-25 | | 6/2X=14 | | 4x-2=58 |

Equations solver categories